Influence of Digital Marketing, Consumer Trust, and Brand Loyalty on Purchase Intention (Case Study of Green Product Consumers) - Desembrianita, Eva; Mulyono, Sri; Putra, Wira Pramana; Tarjono, Tarjono (International Journal of Business, Law, and Education, 2024)
This study explores the influence of digital marketing, consumer trust, and brand loyalty on purchase intention in the context of green product consumers. Utilizing a sample of 248 respondents and employing SmartPLS for data analysis, the research reveals significant positive relationships between the constructs. Digital marketing significantly impacts purchase intention, consumer trust, and brand loyalty, highlighting the importance of effective digital strategies in promoting green products. Consumer trust and brand loyalty are also found to be critical in driving purchase intentions. The findings underscore the need for companies to invest in transparent, ethical, and engaging digital marketing efforts to build long-term consumer relationships and promote sustainable consumption. This study contributes to the literature on green marketing and provides actionable insights for practitioners aiming to increase the adoption of green products.